Effects of nitrogen level on yield and quality of japonica soft super rice - Da-wei ZHU; Hong-cheng ZHANG; Bao-wei GUO; Ke XU; Qi-gen DAI; Hai-yan WEI; Hui GAO; Ya-jie HU; Pei-yuan CUI; Zhong-yang HUO (Journal of Integrative Agriculture, 2017)
Although studies on the balance between yield and quality of japonica soft super rice are limited, they are crucial for super rice cultivation. In order to investigate the effects of nitrogen application rate on grain yield and rice quality, two japonica soft super rice varieties, Nanjing 9108 (NJ 9108) and Nanjing 5055 (NJ 5055), were used under seven N levels with the application rates of 0, 150, 187.5, 225, 262.5, 300, and 337.5 kg ha−1. With the increasing nitrogen application level, grain yield of both varieties first increased and then decreased. The highest yield was obtained at 300 kg ha−1. The milling quality and protein content increased, while the appearance quality, amylose content, gel consistency, cooking/eating quality, and rice flour viscosity decreased. Milling was significantly negatively related with the eating/cooking quality whereas the appearance was significantly positively related with cooking/eating quality. These results suggest that nitrogen level significantly affects the yield and rice quality of japonica soft super rice. We conclude that the suitable nitrogen application rate for japonica soft super rice, NJ 9108 and NJ 5055, is 270 kg ha−1, under which they obtain high yield as well as superior eating/cooking quality.